PENGARUH KONSENTRASI ETHEPHON PADA PROSES DEGREENING BUAH JERUK LEMON (Citrus limon L.) CALIFORNIA - Putranto, Kelik; Haerudjaman, R.; Gunawan, Andri (AGRITEKH (Jurnal Agribisnis dan Teknologi Pangan), 2024)
The color of the peel of the California type lemon when harvested is generally green. Degreening technology using ethepon solution can improve the color of lemon peel to yellow. Degreening is the process of chemically remodeling the green pigment (chlorophyll) in orange peel and forming a yellow color (carotenoids) without affecting the internal quality of the fruit. The study aims to examine the effect of ethepon concentration to stimulate yellow pigments (carotenoids) and its effect on the physicochemical properties of California lemons from Majalengka. Degreening lemons using concentrations of 0 ppm, 200 ppm, 400 ppm, 600 ppm, 800 ppm and 1000 ppm solutions dipped for 10 seconds. Observations were made after one of the treatments had the effect of changing the color of lemons to full yellow (Value 5). Other physicochemical observations include weight loss, total acid, vitamin C and total soluble solids. The results showed that changes in fruit skin color began to occur on day 4 after degreening treatment. The best ethepon concentration is 1000 ppm i.e. it can improve the color quality of lemon fruit from full green to full yellow without negative influence on weight loss, total dissolved solids, vitamin C, and total acid.